Securing a Wireless Site Network to Create a BIM-Allied Work-Front. (22nd August 2014) - Zekavat, Payam R.; Moon, Sungkon; Bernold, Leonhard E.
The Building Information Model (BIM) serves as a framework to align all the project-related data, providing interoperability to store and retrieve information interactively. Unfortunately, the construction site itself is excluded from this interaction as the large amount of data requires high data transfer rates and ruggedized hardware. However, advanced wireless communication technologies open radically new avenues to relay large amounts of data automatically and in near real-time. Construction could be a key beneficiary of these advancements. Wireless communication integrated with BIM, GPS and the Internet is able to provide the backbone necessary for creating intelligent systems, supporting the designer in his or her office as well as workers on the work-front. This paper presents a study that documents the development and testing of prototypes designed to facilitate information sharing at the field-level during construction. The main system constitutes an information hub, called the e CKiosk, connecting "senders and receivers" both on-site as well as off-site. The system design is discussed and some of the main modules are demonstrated. Since the electronic Kiosk depends on robust connections to the wireless devices distributed across the site, reliable connectivity is essential. For this reason, the discussion includes a study of the electronic signals behaviour in an ever-changing construction site. Measurements of the signal strengths during excavation and concrete work are presented and compared with theoretical calculations used to predict wave propagation. The results show how present models overestimate signal attenuation patterns on the construction site. This is important for designing a reliable and secure wireless site networks to link BIM to the work-front.